New advances on disease biomarkers and molecular targets in biomedicine - Lee, Nikki P., (Humana Press :, 2013)
Rising occurrences of various diseases and epidemics have pressurized the already-burdened health system across the globe, and this imposes an unprecedented challenge on our current research in identifying disease-specific biomarkers and molecular targets, in particular for cancers, neurological disorders and unexplained infertility. Despite decades of efforts in deciphering the fundamental biology underlying various diseases at discrete levels using an array of advanced technologies, attempts to identify reliable and disease-indicating markers for detection and biomolecules or cellular structures for targeting are still in vain. This monograph describes and discusses the updated findings in this field with a specific aim to compile prior and recent literature and from there to acquire some insights to facilitate future research to expand our options of understanding, detecting and treating diseases. Among the many possible areas of biomedical research, this content comprises two themes: disease biomarkers and molecular targets. We also cover topics that are more advanced in development to emerging scientific discoveries. In particular, we have included in this monograph concepts on the renovated use of oncofetal molecules in cancer prediction and treatment, the evolving development in cancer biology at the cellular and molecular levels and the recent involvement on new classes of molecules in diseases. We hope that this book can renew established concepts in the field, and at the same time lead to important insights for research and development of drugs, diagnostics, and interventions for managing diseases of unmet medical needs. Non-receptor protein kinases c-Src, c-yes and FAK are biomarkers for male contraceptive research -- Ankyrin repeat and suppressor of cytokine signaling box (ASB) Family members for cancer diagnosis, prognosis, and treatment -- MicroRNA as cancer biomarkers and targets -- Oncofetal molecules as biomarkers and drug targets for hepatic cancer -- Ion channels as novel pancreatic cancer biomarkers and targets -- Circulating biomarkers for sophageal squamous cell carcinoma -- Using genomic biomarkers to predict patient prognosis and treatment response in gastric cancer -- CARF regulates cellular senescence and apoptosis by p53 dependant and independent pathways -- Targeting cancer metabolisms -- Modulation of autophagy as a novel cancer therapeutic strategy -- Functional proteomics screening for novel anti-viral drug targets -- Identification of tumor antigens as targets for novel anti-tumor therapies -- Mesoporous silica nanoparticles for cancer therapy -- Chemoresistance in glioma.